The Impact of Worker Competence and Job Equality on Work Culture (A Study on Outsourcing Workers in the Dumai Integrated Area) - Guntur, Muhamad (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to identify the influence of worker competence and position equality on work culture among outsourcing workers in the Dumai Integrated Development Zone. Worker competence is measured through their skills and knowledge, while position equality refers to workers' perceptions of fair treatment in task distribution and career opportunities. The work culture examined involves the values, norms, and behaviors applied in the work environment. The method used is a quantitative approach with a survey research design. Data was collected through questionnaires distributed to outsourcing workers in the area and analyzed using linear regression techniques to test the relationship between independent and dependent variables. The results indicate that both worker competence and position equality significantly influence the formation of a positive work culture. These findings provide insights for managers and related parties in formulating human resource management policies, particularly for outsourcing workers, to create a more productive and harmonious work environment.